Can miniature accelerometers attached to the gymnastics springboard be used for take-off analysis? - Križaj, D.; Cuk, I. (Science of Gymnastics Journal, 2015)
An investigation of metric characteristic of a device for measuring vault characteristics during the jump on and take-off from the springboard using a miniature Micro-Electro-Mechanical (MEMS) type accelerometer(s) attached onto the springboard is presented. The measured acceleration is integrated once to obtain the velocity of the springboard during the jump and integrated twice to obtain the springboard displacement. Due to several sources of noise the measured signals were filtered using a Butterworth filter of fourth order with a cut off frequency of 250 Hz and a moving average filter. Several parameters of the jump were extracted from the filtered data such as time to maximal springboard compression, maximal positive and negative velocities and times to achieve these velocities. The obtained parameters are evaluated for their variability and reliability by comparing them to the data obtained by a reference high precision laser sensor measuring springboard displacement. The measurement technique is capable of determining several relevant parameters of the springboard usage with an accuracy of less than 5.3 % for all evaluated parameters except for maximal positive velocity for which an error up to 15.3 % has been obtained. Analysis of 43 jumps of single gymnast proved the reliability of the extracted parameters. MEMS accelerometers can thus be used for analysis of the take-off from the springboard taking into account appropriate filtering of the data is performed before extraction of some parameters that are relevant for the analysis.